2004
DOI: 10.1021/ja0394176
|View full text |Cite
|
Sign up to set email alerts
|

Differential Conductance Switching of Planar Tunnel Junctions Mediated by Oxidation/Reduction of Functionally Protected Ferrocene

Abstract: Planar tunnel junctions were fabricated by self-assembling 1,1'- ferrocenedicarboxylic acid (FDCA) onto native oxides of thermally deposited aluminum films and subsequently depositing a second aluminum film. Junctions were characterized using Reflection-Absorption Fourier Transform Infrared Spectroscopy (RAIRS) and current-voltage (I-V) spectroscopy. Before deposition of the second aluminum film, RAIRS of FDCA and ferrocenecarboxylic acid (FCA) films revealed COO(-), C=O, and Fc ring stretching modes, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 86 publications
1
26
0
Order By: Relevance
“…The sCA of Fc-terminated mica-DA monolayer is 45°, while Fc + -terminated dopamine monolayer has a lower CA of 23°due to more hydrophilic nature of the oxidized Fc + (Fig. 8a, inset), correlating well with the determined surface chemical composition [57]. X-ray photoelectron spectroscopy (XPS) was performed on the Si-DA (in black) and Si-DA-Fc (in red) to further verify the surface composition.…”
Section: Derivation Reaction Of Dopamine Monolayersupporting
confidence: 54%
“…The sCA of Fc-terminated mica-DA monolayer is 45°, while Fc + -terminated dopamine monolayer has a lower CA of 23°due to more hydrophilic nature of the oxidized Fc + (Fig. 8a, inset), correlating well with the determined surface chemical composition [57]. X-ray photoelectron spectroscopy (XPS) was performed on the Si-DA (in black) and Si-DA-Fc (in red) to further verify the surface composition.…”
Section: Derivation Reaction Of Dopamine Monolayersupporting
confidence: 54%
“…Under electrochemical conditions, this kind of molecules exhibits interesting switching properties though the control of its ferrocene redox state. [81,[86][87][88] The dissymmetric monothiol parent of this molecule exhibits a fast redox reaction when self-assembled on gold electrodes, [89,90] establishing that electron transport is very efficient through this kind of molecule. Figure 10 shows three typical I-V curves for molecular junctions involving Fc-VPM molecules and different gap widths.…”
Section: Ec-mcbj Study Of Molecular Junctionsmentioning
confidence: 99%
“…The molecule is a good model system for studying electron transport phenomena also because it exhibits fast and reversible one-electron transfer on gold and other solid electrodes. Recent experiments have shown that ferrocene compounds exhibit negatively differential resistance (NDR) effect, which further demonstrates rich and interesting electronic properties of the molecule [25,[27][28][29]. In the present work, our focus is to determine how the conductance of ferrocene compounds chemically bound to two probing electrodes depends on the redox states.…”
Section: Introductionmentioning
confidence: 96%